2011
DOI: 10.1016/j.ejcts.2011.01.080
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sequestration: a retrospective analysis of 2625 cases in China

Abstract: Clinical manifestations of pulmonary sequestration varied and preoperative diagnosis was often incorrect. To improve the preoperative diagnosis rate, we should take full advantage of symptoms, image performance, and localization characteristics. A certain early-onset age, recurrent pneumonias, mass or cyst lesion located in the lower lobe, and aberrant arterial supply are indicators for the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
181
1
32

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(227 citation statements)
references
References 13 publications
(13 reference statements)
13
181
1
32
Order By: Relevance
“…Almost 90% of ELS occur in the left hemithorax, and 10% of them may present below the diaphragm. Bilateral sequestrations are uncommon, and only three cases had previously been reported; two of these were ILS and one was mixed ILS and ELS [10,11]. In the present study, 78.9% of cases were ILS and 84.2% of our cases were located in the left lower lobe.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Almost 90% of ELS occur in the left hemithorax, and 10% of them may present below the diaphragm. Bilateral sequestrations are uncommon, and only three cases had previously been reported; two of these were ILS and one was mixed ILS and ELS [10,11]. In the present study, 78.9% of cases were ILS and 84.2% of our cases were located in the left lower lobe.…”
Section: Discussionmentioning
confidence: 58%
“…ILS constitutes 75 to 90% of BPS [1,9], and the ELS/ ILS ratio is higher in children than in adults. Wei found that BPS is mainly located in the lower lobes, especially in the left lower lobe (71.53%) [10]. Almost 90% of ELS occur in the left hemithorax, and 10% of them may present below the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several reports on extralobar pulmonary sequestration in human, but only a few reports of occurrence of this anomaly are present in the veterinary literature [4][5][6] . In humans, pulmonary sequestration represents between 0.15% and 6.45% of all pulmonary malformations [7,8] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, later development of the accessory lung bud results in the extralobar type [2,17,18] . A spiral CT with contrast angiography and magnetic resonance imaging (MRI) are the diagnostic techniques of choice [5,7,11,[19][20][21][22][23][24][25][26] . The treatment of an extralobar sequestrum is mainly by surgical excision which removes the mass completely total of the sequestrum to reduce the risk of repeated infection [2,5,7,19,20,[27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…The intralobar type accounts for approximately 75% of cases; extralobar pulmonary sequestration accounts for 25% of cases, is located extrapulmonarily and forms its own visceral pleura. 3,4 The majority of these lesions are diagnosed in children; intrauterine diagnosis using prenatal ultrasound and magnet resonance imaging are available. 5 Intrauterine interventional procedures are an exciting new therapeutic option.…”
mentioning
confidence: 99%